Scott at the opera: interpreting Das Opfer (1937) - Leane, E; Philpott, C; Nielsen, H (The Polar Journal, 2014)
In November 1937, an unusual work premiered at the Hamburg State Opera.Entitled Das Opfer (The Sacrifice), the one-act opera tells the story of RobertF. Scotts last expedition, focusing on the famous final moments of LawrenceOates. While the action features only four main characters, a large chorus dressed for much of the time in penguin costumes comments on events. Theopera was an adaptation of an award-winning and controversial play by theeccentric expressionist poet Reinhard Goering. The libretto was written by Goering,who committed suicide not long after its completion about a year beforethe first performance. The score was by composer Winfried Zillig a student ofArnold Schoenberg and promoter of his radical modernist 12-tone technique.Subsequent descriptions of Das Opfer and its reception have been remarkablyvaried. Some commentators assert the play was quickly banned by the NationalSocialists due to its pro-British content and degenerate 12-tone score. Othersargue that this version of events was invented post-war in order to distance Zilligfrom the Nazi regime, which actually embraced his work, including Das Opfer.Given that Das Opfer was probably the first professional musical response toScotts last expedition, and certainly the first operatic performance of the story, itis surprising that no in-depth contextual account of the work is available. Theaim of our research is to provide an analysis of this opera historical, textualand musical that is both relevant to an Antarctic studies readership and accessibleto English-speaking readers. In doing so, we suggest tentative answers tosome questions raised by this intriguing musical work: How was Scotts expedition,which has so often been tied to ideas of Britishness, adapted for Germanaudiences? And what significance did the operas Antarctic setting hold in thiscontext?